From Tradition to Innovation: Tokenizing Dinar and Dirham for the Islamic Digital Economy - Hutagalung, Muhammad Wandisyah R; Mairiza, Diany (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This research explores the potential and implications of tokenizing Dinar and Dirham in the context of Islamic digital finance, with a focus on the use of blockchain technology to facilitate their integration into the global financial system. The study adopts a qualitative approach, analyzing data derived from scholarly publications, online resources, and case studies from countries like the UAE and Malaysia, which are exploring blockchain-based Islamic currencies. The research examines the fundamental principles of Dinar (gold) and Dirham (silver) as intrinsic-value currencies within Islamic finance, highlighting their alignment with Sharia principles such as transparency, fairness, and the prohibition of riba (interest). Furthermore, the study explores the concept of tokenization, its application in the digital economy, and its potential to offer stable, inflation-free payment solutions.Key findings indicate that tokenized Dinar and Dirham can enhance financial inclusion, promote economic stability, and provide an alternative to volatile fiat currencies. Blockchain technology is identified as an effective platform for supporting these tokenized currencies, ensuring transparency, security, and decentralization in compliance with Sharia law. However, the research also identifies several challenges, including regulatory uncertainties, technological scalability issues, and societal resistance to adopting digital currencies. Drawing on case studies, the research highlights the importance of clear regulatory frameworks, technological advancements, and financial literacy programs to support the widespread adoption of tokenized Islamic currencies.The study concludes with policy recommendations aimed at addressing these challenges, emphasizing the need for a collaborative approach involving regulators, financial institutions, and technology providers. Future research directions include exploring the practical implementation of tokenized Dinar and Dirham and examining consumer behavior and the broader economic impact of these digital currencies. This research contributes to the growing discourse on Islamic digital finance and offers insights into how tokenized Dinar and Dirham can potentially reshape the future of finance in Muslim-majority countries. Keywords: Tokenization, Dinar, Dirham, Blockchain, Islamic Finance, Digital Currency, Sharia Compliance.